Pulmonary hyalinising granuloma: a rare and elusive cause of multiple lung nodules. Issue 3 (25th March 2020) - Tang, Ivan; Moore, Alastair J; Fryer, Eve; Sykes, Annemarie
Abstract : A 72-year-old woman was referred with incidentally detected multiple lung nodules, one of which was identified as 18 F-fluorodeoxyglucose (FDG)-avid on positron emission tomography. Extensive workup followed, including numerous radiographs, surveillance scans and a CT-guided biopsy which demonstrated chronic inflammation only. Following a wedge-resection, a diagnosis of pulmonary hyalinising granuloma (PHG) was made. PHG is a cause of FDG-avid single or multiple pulmonary nodules and can mimic lung cancer or metastatic disease radiologically. The diagnosis is often difficult to make with minimally invasive techniques such as needle-guided biopsies which do not tend to yield the diagnosis and requires surgical resection for definitive diagnosis and exclusion of malignancy.